Morbidity and mortality associated with emergency obstetric hysterectomy: a three year retrospective study in a tertiary care centre of India - ., Swati; ., Vineeta; Aslami, Ahmad Nadeem (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Emergency obstetric hysterectomy (EOH) continues to remain an important life saving procedure in the era of modern obstetrics. EOH acts as a near miss marker as a proxy for maternal mortality. The objective of this study was to analyze 52 EOH done in a tertiary care centre of Ajmer, Rajasthan, India. Methods: A retrospective study was done using hospital records of 52 EOH done in a three year period in the Department of Obstetric and Gynaecology, LNJ Medical College, Ajmer, Rajasthan, India. Results: The incidence of obstetric hysterectomy was 1.25 in 1000 deliveries. The average age of the patients was 27.8 years. Most common reason for EOH was post partum haemorrhage (PPH). 86.5% patients went under subtotal hysterectomies. Several complications occurred in these patients, severe anemia being most common. 28.8% patients died after the operations. More than half patients delivered a live baby while 40.4% had still births. Conclusions: EOH is a life saving procedure. The outcome depends on timely decision and apt clinical judgement because delay can lead to high maternal as well as infant mortality.